Impact of Advertising Media Cigarette Packaging on Adolescent Smoking Behavior - Sudirman; Ahmad Yani; Moh. Fikri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Adolescent smoking behavior is a deviant act that can harm the teenager and those around him. The influence of chemicals contained by cigarettes such as Nicotine, Carbon Monoxide, and Tar will spur the work of the central nervous system and sympathetic conditions, resulting in increased blood pressure and increased heart rate. This study aims to determine the impact of cigarette advertising media on the smoking behavior of adolescents, especially in Talise Village. This research uses a qualitative type of research. The results of this study show that the advertising media in cigarette packaging does not affect the smoking behavior of adolescents because the advertising media packaged cigarettes are not very clear and are often improved because of the support of parents who are indirectly active smokers and also have an effect on peers.